Efficiency Analysis of Sheep Farms in Cyprus - Sokratis Sokratous; Athanasios Ragkos; Georgios Arsenos; Alexandros Theodoridis (Agriculture)
In this study, an empirical analysis was applied to measure the efficiency level of dairy farms in Cyprus and estimate the capacity of sheep farmers to support the increasing demand for halloumi cheese. Data Envelopment Analysis was used on data from 50 dairy sheep farms in Cyprus, which operate under extensive, semi-intensive, and intensive systems. The main features of the most efficient farms are presented, and a comparative financial analysis is implemented between the efficient and less efficient farms. The results indicate room for improvement in extensive and semi-intensive dairy sheep farming and verify that the transition that takes place in sheep farming towards more intensive systems constitutes the optimal approach. The most efficient farms operate under semi-intensive and intensive dairy sheep farming and achieve higher milk yields than the farms operating under extensive systems. Feeding constitutes the main cost driver, exceeding 60% in both efficient and inefficient farms, while labor wages and fixed capital cost varies between 25% and 30% of the total production cost for both efficiency groups. The findings indicate that the farms should utilize economies of scale to reduce production costs and utilize fixed capital endowments at full capacity.